The Influence of Workload, Teamwork, and Performance Discipline on Employees in the Karya Sukses (Gresik) Synergy Cv - Mohammad Andi Firmansyah; M Sihab Ridwan (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the effect of workload, teamwork, and work discipline on employee performance at CV SINERGI KARYA SUKSES (GRESIK). The number of samples used in this study were 40 respondents. The method in this study used the validity test, reliability test and classic assumption test, data analysis was carried out by Multiple Linear Regression Analysis and Determination Coefficient Analysis (R²), while the hypothesis testing technique used the t test and F test. The results showed that simultaneously (Test F) Workload (X1), Teamwork (X2), and Work Discipline (X3) have a significant effect on Employee Performance (Y) CV. SINERGI KARYA SUCCESS. The effect of each variable partially (t test), the results of the significance value of: 1) Workload (X1) partially has a significant negative effect on employee performance (Y). 2) Teamwork (X2) partially has a significant positive effect on Employee Performance (Y). 3) Work Discipline (X3) partially has a significant positive effect on Employee Performance (Y). Suggestions for future researchers with the same type of research to add the time period used. So that the results obtained can be better and more accurate.